The complete chloroplast genome sequence of the Sechium edule (Jacq.) Swartz. (Cucurbitaceae). Issue 1 (2nd January 2021) - Cui, Haonan; Zhu, Zicheng; Lu, Zhaokai; Ding, Zhuo; Zhang, Chen; Luan, Feishi
Abstract: Sechium edule (Jacq.) Swartz is an important vegetable with both food and medicinal values. The complete chloroplast genome sequence of S. edule has been reported in this study. The total genome size is 154, 558 bp in length and contains a pair of inverted repeats (IRs) of 19, 128 bp, which were separated by large single-copy (LSC) and small single-copy (SSC) of 98, 806 and 17, 496 bp, respectively. A total of 122 genes were predicted including 78 protein-coding genes, 8 rRNA genes, and 36 tRNA genes. Further, the phylogenetic analysis confirmed that S. edule belongs to the family Cucurbitaceae. The complete chloroplast genome of S. edule would play a significant role in the development of molecular markers for plant phylogenetic and population genetic studies.